1992
DOI: 10.2166/wst.1992.0057
|View full text |Cite
|
Sign up to set email alerts
|

Production and Reduction of Geosmin and 2-Methylisoborneol During Storage of River Water in Deep Reservoirs

Abstract: The Water Storage Corporation Brabantse Biesbosch manages three interconnected deep reservoirs in the south western part of The Netherlands. These reservoirs, with a total retention period of five to six months, are employed for storage and upgrading of polluted and eutrophic water from the River Meuse. In the first two reservoirs, with a total retention period of 4-5 months, probably due to adsorption/settling and biodegradation there is a reduction of geosmin and 2-methylisoborneol (2-MIB) down to 1-2 ng/l, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…The GSM concentration was higher in the reservoirs (5–7100 ng L −1 ) and shallow water than in the streams (4–24 ng L −1 ), with a high frequency and extent of the Dolichospermum bloom ( Appendix A ). Generally, the GSM concentrations in the reservoirs decreased (60–70% of influent water) primarily because of adsorption, sedimentation, and biodegradation (3.1 ng L −1 d −1 ), as described in a previous study [ 25 ]. However, if internal productivity is high (e.g., dense bloom) because of aggravated anthropogenic pollution factors, efforts to improve water quality may have adverse effects, which is intensified in eutrophic water bodies with shallow water depths [ 25 ].…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The GSM concentration was higher in the reservoirs (5–7100 ng L −1 ) and shallow water than in the streams (4–24 ng L −1 ), with a high frequency and extent of the Dolichospermum bloom ( Appendix A ). Generally, the GSM concentrations in the reservoirs decreased (60–70% of influent water) primarily because of adsorption, sedimentation, and biodegradation (3.1 ng L −1 d −1 ), as described in a previous study [ 25 ]. However, if internal productivity is high (e.g., dense bloom) because of aggravated anthropogenic pollution factors, efforts to improve water quality may have adverse effects, which is intensified in eutrophic water bodies with shallow water depths [ 25 ].…”
Section: Discussionsupporting
confidence: 52%
“…Generally, the GSM concentrations in the reservoirs decreased (60–70% of influent water) primarily because of adsorption, sedimentation, and biodegradation (3.1 ng L −1 d −1 ), as described in a previous study [ 25 ]. However, if internal productivity is high (e.g., dense bloom) because of aggravated anthropogenic pollution factors, efforts to improve water quality may have adverse effects, which is intensified in eutrophic water bodies with shallow water depths [ 25 ]. In addition, GSM in stratified reservoirs with discharge systems in deep layers (middle or bottom) are mostly concentrated just below these layers, and effluents after destratification by turnover can hinder water use for several months [ 83 ].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In view of the history of O. limosa with respect to MIB problems, it is reasonable to consider it a potential source of MIB in DVL also. Other investigators have reported geosmin from this species (Van Breemen et al, 1992;Durrer et al, 1999;Sabater et al, 2003), but it is uncertain whether they all referred to the same organism. Various studies in the last twenty years have implicated other attached cyanobacteria as sources of MIB or geosmin in lakes, reservoirs or rivers, including Burlingame et al (1986), Sugiura et al (1998), Watson and Ridal (2004) and Baker et al (2006).…”
Section: Resultsmentioning
confidence: 92%